2016
DOI: 10.5902/1983465918169
|View full text |Cite
|
Sign up to set email alerts
|

Gestão estratégica de pessoas e comprometimento organizacional em organizações hospitalares

Abstract: This research is characterized as a qualitative approach based on multiple-case studies in hospital organizations. These findings enhance our understanding of how the strategic management of people can foster organizational commitment, using managers of hospital organizations as subjects, and expanding discussions about the concept of organizational commitment. Data were collected using in-depth interviews, qualitative survey questionnaires and documentary research. Data management and analysis were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Thus, it can be confirmed in this research, the findings of Silva et al (2016), because they found evidence that organizational commitment is composed of elements of attitudinal nature that includes beliefs, affections and intentions, as well as behavioral elements, which are the attitudes generated by the commitment, as the budget participation had positive effects on the organizational commitment and this with the managerial performance. Therefore, such characteristics of organizational commitment, addressed by Silva et al (2016), are present in the managers with budget responsibilities researched in the study.…”
Section: Discussion Of the Results: Motivational Effects Of The Budgetary Participation On Managerial Performancesupporting
confidence: 73%
“…Thus, it can be confirmed in this research, the findings of Silva et al (2016), because they found evidence that organizational commitment is composed of elements of attitudinal nature that includes beliefs, affections and intentions, as well as behavioral elements, which are the attitudes generated by the commitment, as the budget participation had positive effects on the organizational commitment and this with the managerial performance. Therefore, such characteristics of organizational commitment, addressed by Silva et al (2016), are present in the managers with budget responsibilities researched in the study.…”
Section: Discussion Of the Results: Motivational Effects Of The Budgetary Participation On Managerial Performancesupporting
confidence: 73%